The effect of acute exercise and gender on the levels of irisin in elite athletes - Ankan, S. (Physical Education of Students, 2018)
Purpose: Irisin is defined as a myokine secreted by skeletal muscle contraction. Myokines are associated with energy metabolism and muscle regeneration capacity. They provide support for active muscles with acute or regular exercises. The aim of this study was to determine the effect of acute exercise on the hormone levels of irisin in taekwondo athletes. Material: Thirteen volunteer elite taekwondo athletes (7 males, 6 females) participated in the study between the ages of 16-20. At the beginning of the study, participants` body compositions were determined. Blood samples were taken before and after acute exercise at 8:00 am after overnight fasting. Plasma irisin hormone analyzes were determined by Enzyme-Linked Immuno Sorbent Assay (ELISA) method. The analysis of the data was tested with two-factor (time-gender) analysis of variance in repeated measures. Results: Significant differences were found between body weight, height and body fat percentage in both male and female athletes (p<0.05). There was no significant difference between the averages of age, sports experience and body mass index (p>0, 05). The effect of acute exercise and gender on irisin levels was not significant (p>0.05). Conclusions: As a result, it can be said that acute exercise and gender did not affect the hormone levels of irisin in elite taekwondo athletes.